2008
DOI: 10.1097/rct.0b013e31815ea857
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Cirrhosis by Spiral Computed Tomography

Abstract: Spiral CT demonstrates high accuracy and interobserver agreement in the diagnosis of cirrhosis, suggesting CT may be a supplementary diagnostic test in patients who have contraindications to biopsy or have equivocal biopsy findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 18 publications
(18 reference statements)
0
4
0
Order By: Relevance
“…The use of subjective LSN to stage liver fibrosis has been also applied to computed tomography (CT) [10], [11] and magnetic resonance imaging (MRI) [6] with varying levels of reported diagnostic accuracy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of subjective LSN to stage liver fibrosis has been also applied to computed tomography (CT) [10], [11] and magnetic resonance imaging (MRI) [6] with varying levels of reported diagnostic accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…The use of liver morphology, specifically by subjectively evaluating liver surface nodularity (LSN), to stage liver fibrosis has been well studied in ultrasound imaging, with varying levels of diagnostic accuracy for predicting liver fibrosis stage reported in the literature [7] , [8] , [9] . The use of subjective LSN to stage liver fibrosis has been also applied to computed tomography (CT) [10] , [11] and magnetic resonance imaging (MRI) [6] with varying levels of reported diagnostic accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1 ] Current modalities including elastography, laboratory biomarkers, and subjective LSN stage system are not qualified to replace the reference standard of invasive liver biopsy, as a result of limited accuracy, dedicated equipment requirement, and interobserver variability. [ 18 ] Recent studies have developed and validated a new semiautomated software equipped with quantitative tool for deriving objective scores of LSN on multidetector computed tomography (MDCT) and MRI for predicting early cirrhosis, [ 12 , 13 , 19 ] obviating the invasive liver biopsy and the drawbacks of previous methods with varied diagnostic performance. To our knowledge, there has been no previous meta-analysis evaluating the diagnostic performance of quantitative LSN score for predicting early cirrhosis based on imaging procedures, additionally, no consensus has been reached about the diagnostic accuracy of LSN with varied cut-off values.…”
Section: Discussionmentioning
confidence: 99%
“…There is growing evidence that the morphologic change of liver surface nodularity (LSN) based on imaging modalities is associated with the severity of CLD, which has been applied in US, [ 9 11 ] computed tomography (CT), and MRI, [ 12 , 13 ] recent studies demonstrated that quantitative LSN score using these novel imaging techniques has the potential to predict the early cirrhosis stage (F4). [ 14 , 15 ] Whereas, the results of these studies are insufficiently robust with a small sample size, and no clear consensus has been reached about the diagnostic accuracy of LSN score with varied cut-off values; in addition, there has been no previous published meta-analysis evaluating the diagnostic performance of quantitative LSN score based on imaging procedures.…”
Section: Introductionmentioning
confidence: 99%